2020
DOI: 10.2174/1389200221666200711155632
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Bromhexine and its Active Metabolite - Ambroxol as Potential Analgesics Reducing Oxaliplatin-induced Neuropathic Pain - Pharmacodynamic and Molecular Docking Studies

Abstract: Background: Painful peripheral neuropathy is a dose-limiting adverse effect of the antitumor drug oxaliplatin. The main symptoms of neuropathy: tactile allodynia and cold hyperalgesia, appear in more than 80% of patients on oxaliplatin therapy and are due to the overexpression of neuronal sodium channels (Navs) and neuroinflammation. Objective: This study assessed antiallodynic and antihyperalgesic pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 68 publications
0
13
0
Order By: Relevance
“…In the von Frey test, significant differences were noted between the pre-drug paw withdrawal threshold in the early phase of the study and the pre-drug paw withdrawal threshold in the late phase of the study (day 7 after oxaliplatin) for repeated-dose ambroxol (90 mg/kg). This finding indicated that the repeated administration of this drug partially attenuated the tactile allodynia caused by oxaliplatin [41].…”
Section: Effect Of Minocycline Combined With Ambroxol On Tactile Allo...mentioning
confidence: 69%
See 2 more Smart Citations
“…In the von Frey test, significant differences were noted between the pre-drug paw withdrawal threshold in the early phase of the study and the pre-drug paw withdrawal threshold in the late phase of the study (day 7 after oxaliplatin) for repeated-dose ambroxol (90 mg/kg). This finding indicated that the repeated administration of this drug partially attenuated the tactile allodynia caused by oxaliplatin [41].…”
Section: Effect Of Minocycline Combined With Ambroxol On Tactile Allo...mentioning
confidence: 69%
“…In our recent study [41], we demonstrated that intraperitoneal ambroxol (90 mg/kg) used as a single or repeated dose attenuated tactile allodynia in oxaliplatin-treated mice. In the von Frey test, significant differences were noted between the pre-drug paw withdrawal threshold in the early phase of the study and the pre-drug paw withdrawal threshold in the late phase of the study (day 7 after oxaliplatin) for repeated-dose ambroxol (90 mg/kg).…”
Section: Effect Of Minocycline Combined With Ambroxol On Tactile Allo...mentioning
confidence: 85%
See 1 more Smart Citation
“…ROS also induce the release of Ca 2+ by activating inositol 1,4,5-trisphosphate receptors (IP3R) to open the permeability transition pore, thereby changing the permeability of mitochondria to further release more ROS as a vicious cycle ( Csordas and Hajnoczky, 2009 ; Kiselyov and Muallem, 2016 ). Moreover, voltage-gated sodium (NaV) channels play a role in initiating action potentials in DRG neurons, whose surface modification affects neuronal electrical excitability and participate in the development of cold abnormal pain ( Furgala-Wojas et al, 2020 ). For example, Pt drugs prolong Nav1.6 open times and increase persistent current in DRG neurons, which aggravate cold abnormal pain ( Sittl et al, 2012 ).…”
Section: Reactive Oxygen Species-related Mechanism Of Platinum-induced Peripheral Neuropathymentioning
confidence: 99%
“…The calculation procedures applied in the study are typical for processing of docking studies [63,[89][90][91].…”
Section: Docking Studymentioning
confidence: 99%